Analisis Efisiensi Puskesmas di Kabupaten Sumbawa Tahun 2015 - Binar Dwiyanto Pamungkas; Wahyunadi Wahyunadi; M. Firmansyah (Universitas Negeri Malang, 2016)
The focus of this study is measuring relative efficiency of 23 public health centers in Sumbawa regency in 2015, by using non parametric approach Data EnvelopmentAnalysis (DEA). DEA is chosen because it is able to handle more input and output variables. This study uses output oriented model. Input variables consist of numbers of medical staf, numbers of other medical staf, number of capitation funds, operational funds health,. Output variables consist of numbers of visitor, Case Detection Rate TBC, safe motherhood, infant’s imunization coverage, percentage of child under five’s weighting, and coverage of active family planning. The results are 18 public health centers classified as technically efficient and the remaining classified as technically inefficient in 2015 For the public health centers which are technically inefficient can be improved by increasing output variable based on DEA.Keywords: Relative efficiency, Public health center, DEAJEL Classification: C14, D61